Multiple Cross Displacement Amplification Coupled With Nanoparticles-Based Lateral Flow Biosensor for Detection of Staphylococcus aureus and Identification of Methicillin-Resistant S. aureus - Wang, Yi; Yan, Weiqiang; Fu, Shanshan; Hu, Shoukui; Wang, Yan; Xu, Jianguo; Ye, Changyun (Frontiers in Microbiology, 2018)
Staphylococcus aureus (S. aureus), including methicillin-resistant S. aureus (MRSA), is one of the most important human pathogens, which is responsible for bacteremia, soft-tissue infections and food poisoning. Hence, multiple cross displacement amplification (MCDA) is employed to detect all S. aureus strains, and differentiate MRSA from methicillin-sensitive S. aureus (MSSA). Multiplex MCDA (m-MCDA), which targets the nuc gene (S. aureus-specific gene) and mecA gene (encoding penicillin-binding protein-2’), could detect S. aureus strains and identify MRSA within 85 min. Detection of the m-MCDA products is achieved using disposable lateral flow biosensors (LFB). Fifty-eight strains, including various species of Gram-positive and Gram-negative strains, are used for evaluating and optimizing m-MCDA assays. The optimal amplification condition is found to be 63°C for 40 min, with detection limits at 100 fg DNA/reaction for nuc and mecA genes in the pure cultures, and 10 CFU/tube for nuc and mecA genes in the blood samples. The analytical specificity of m-MCDA assay is of 100%, and no cross-reactions to non-S. aureus strains are produced according to the specificity testing. Particularly, two additional components, including AUDG enzyme and dUTP, are added into the m-MCDA amplification mixtures, which are used for eliminating the unwanted results arising from carryover contamination. Thus, the m-MCDA technique appears to be a simple, rapid, sensitive and reliable assay to detect all S. aureus strains, and identify MRSA infection for appropriate antibiotic therapy.